Analisa Angkutan Sedimen Pada Hulu Bendung Aepodu Kabupaten Konawe Selatan - Putra, Ramadhan Hidayat; Syukri, Amad Syarif; Sudarjat, Catrin; Ilham, Vickky Anggara (Universitas Sulawesi Tenggara, 2021)
Research on Aepodu Weir Sediment Transport Analysis in South Konawe District, based on observations in the field, Aepodu Weir has a sediment buildup that has now exceeded the height of the weir light house. The purpose of the study was to analyze the magnitude of Aepodu river flow and to analyze the amount of sediment transport that occurred in the Aepodu dam. The method used to determine the amount of bed load transport uses stchoklitscht, while for transporting suspended load using forcheimer. The results of the analysis of the average flow of the Aepodu river were 3,604 m3 / second. Sediment transport that occurs in Aepodu weir is Bedload transport (Qb) of 291625.771 tons / year, and suspended load transport (Qs) of 16972,423 tons / year, so that the total sediment transport (QT) is 308598,194 tons / year.